Changing circumpolar distributions and isoscapes of Antarctic krill: Indo‐Pacific habitat refuges counter long‐term degradation of the Atlantic sector. Issue 1 (21st September 2020) - Yang, Guang; Atkinson, Angus; Hill, Simeon L.; Guglielmo, Letterio; Granata, Antonia; Li, Chaolun
Abstract: The Southern Ocean provides strong contrasts in rates and directions of change in temperature and sea ice between its sectors, but it is unknown how these affect plankton species that are distributed right around Antarctica. Here, we quantify the changing circumpolar distributions of Antarctic krill, based on the CHINARE 2013/14 circum‐Antarctic expedition, plus independent analyses of compiled abundance data (KRILLBASE: 1926–2016). In the 1920s–1930s, average krill densities in the Atlantic‐Bellingshausen sector were eight times those in the other sectors. More recently, however, the concentration factor has dropped to only about twofold. This reflects a rebalancing broadly commensurate with climatic forcing: krill densities declined in the Atlantic‐Bellingshausen sector which has warmed and lost sea ice, densities may have increased in the Ross‐Pacific sector which showed the opposite climatic trend, while densities showed no significant changes in the more stable Lazarev‐Indian sectors. Such changes would impact circumpolar food webs, so to better define these we examined circumpolar trends of isotopic values in krill and other zooplankton based on the CHINARE cruise and a literature meta‐analysis. Krill δ 15 N values ranged significantly between sectors from 2.21‰ (Indian) to 3.59‰ (Ross‐Pacific), about half a trophic level lower than another key euphausiid, Thysanoessa macrura . These isoscapes form a baseline for interpreting the reliance of predators on euphausiids, within the varying food webs around the continent. Overall, we suggest that the Indo‐Pacific sector has acted as a refuge for the circumpolar krill stock while conditions for them deteriorated rapidly in the Atlantic sector.